Mucocutaneous Manifestations of Behçet's Disease - Nakamura, Koichiro; Tsunemi, Yuichiro; Kaneko, Fumio; Alpsoy, Erkan (Frontiers in Medicine, 2021)
Behçet’s disease (BD) is a chronic, relapsing, systemic inflammatory disease with clinical features showing mucocutaneous lesions and ocular, articular as well as further miscellaneous organ involvement. Mucocutaneous manifestations, one of the most characteristic signs of BD, have been the most common symptoms at the onset or any stage of the disease and are exceptionally important in its diagnosis. Given the lack of specific diagnostic laboratory tests for BD, diagnosis is based on clinical findings. All the diagnostic criteria published have thus far relied heavily on mucocutaneous manifestations, particularly oral and genital ulcers, cutaneous lesions and pathergy test positivity. Worldwide, oral and genital ulcers, cutaneous lesions, ocular and articular manifestations have been the most common symptoms, with erythema nodosum-like lesions and papulopustular lesions being the most prevalent cutaneous manifestations. While majority of the patients worldwide have reported oral ulcers as the most frequent symptom upon disease onset, genital ulcers and erythema nodosum-like lesions have also been identified upon onset. Considering that mucocutaneous symptoms precede severe organ involvement in most patients, and that sometimes they are the only sign of the disease, familiarity with the mucocutaneous symptoms is imperative for early diagnosis and prevention from potentially serious organ involvement through appropriate management.